Penicillium menonorum, a new species related to P. pimiteouiense - S.W. Peterson; S.S. Orchard; S. Menon (IMA Fungus)
Penicillium menonorum is described as a new monoverticillate, non-vesiculate species that resembles P. restrictum and P. pimiteouiense. On the basis of phylogenetic analysis of DNA sequences from four loci, P. menonorum occurs in a clade with P. pimiteouiense, P. vinaceum, P. guttulosum, P. rubidurum, and P. parvum. Genealogical concordance analysis was applied to P. pimiteouiense and P. parvum, substantiating the phenotypically defined species. The species P. rubidurum, P. guttulosum, and P. menonorum were on distinct branches statistically excluded from inclusion in other species and have distinct phenotypes.